Evaluation of seismic performance and design of AAC building systems (autoclaved aerated concrete) with different reinforcement methods (Nexo Revista Científica, 2023)
Autoclaved lightweight concrete was produced for the first time in Sweden and after several decades, it has been widely used in most of the industrialized countries of the world, especially in the construction industry. Lightness, effect in reducing forces caused by earthquakes, ease of implementation, low thermal coefficient, fire resistance and sound insulation are among the undeniable advantages of this product. The use of this concrete is very effective in optimizing fuel and energy consumption, and its high compressive strength is considered an important feature, to the extent that it has been recognized as a desirable and suitable product in the construction industry. Obviously, with the growth of demand increasingly, using traditional methods and materials for housing production in Iran is not very effective. Compilation of criteria for the design and implementation of a gravity-bearing and lateral structural system made of AAC autoclaved aerated concrete products (including reinforced blocks and panels) The structure is made based on valid international regulations and considering Iran's seismic standards as follows. Roof and floor design using reinforced AAC roof panels and the combination of AAC roof blocks and regular concrete in place reinforced with steel reinforcements after examining the principles and foundations and modeling based on logical engineering principles and assumptions to compare the results and the outputs of the software have paid. Based on the available results, we can see the effect of the number of floors, plan and height of the floor on the behavior of the structure. According to the values in the table, the probability of the structure passing through the threshold of minor, moderate, and advanced damage is examined in different states. 1- The probability of passing a 1-story structure compared to a 2-story structure from the threshold of partial, moderate, and advanced damage has decreased by 59.7%, 94.5%, 99.3, and 99.8%, respectively. 2- The probability of passing a 2-story structure compared to a 3-story structure It reduces the threshold of partial, moderate, and advanced damage by 55.7%, 93.2%, 99.0%, and 99.7%, respectively.